PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP PEMBELIAN IMPULSIF ( Studi kasus pada Kedaiku Dimsum Pasir Pengaraian ) - Yuli Setya Rodlotul Jannah; Triyani Capeg Hadmandho; Andi Lesmana (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to determine or how to see the influence of promotions and product quality on impulsive purchases at my Dimsum shop in Pasir Pengaraian. This study was conducted using a purposive sampling method, the population in this study were buyers of my dimsum shop, the sample used in this study was 155 people. The variables in this study consisted of 2 independent variables, namely Promotion, as a variable (X1), Product Quality as a variable (X2), and the dependent variable, namely Impulsive Purchase as a variable (Y). The data collection technique used a questionnaire. Data analysis used the SmartPLS 4.1.9.2 program. The results obtained in this study are, the independent variable Promotion is proven to have a significant effect on the dependent variable Impulsive Purchase, the independent variable product quality is proven to have a significant effect on the dependent variable impulsive purchase. Then it can be seen that both independent variables studied simultaneously affect the dependent variable impulsive purchase. My dimsum shop needs to maintain or improve promotions and product quality so that consumers or customers always buy dimsum products at my Dimsum shop in Pasir Pengaraian.